Pediatric Urolithiasis: Current Surgical Strategies and Future Perspectives - Paraboschi, Irene; Gnech, Michele; De Marco, Erika Adalgisa; Minoli, Dario Guido; Bebi, Carolina; Zanetti, Stefano Paolo; Manzoni, Gianantonio; Montanari, Emanuele; Berrettini, Alfredo (Frontiers in Pediatrics, 2022)
New scientific developments and technological innovations have led to significant changes in the surgical management of pediatric urolithiasis. Miniaturized technologies and minimally invasive approaches have been increasing used in pediatric urology to minimize surgical complications and improve patient outcomes. Moreover, three-dimensional modeling reconstructions, virtual, augmented and mixed reality are rapidly pervading the field of urological interventions, equipping surgeons with powerful tools capable of enhancing the surgical visualization of anatomical normal and pathological structures. Novel optical imaging systems and various simulators offered by the new technologies of the digital era have become a new hope. The use of new strategies in surgical planning and treatment processes has opened new horizons for patients and surgeons. These novel imaging techniques and devices represent the future of urology, and they are fast approaching clinical implementation. There is a wide range of possibilities in the adult population to use these novel technologies and devices in the guidance for urological procedures and minimally invasive surgeries. Their applications and their use have also been increasingly growing in the field of pediatric urology, where the detailed visualization of small anatomical structures could reduce the procedure time, minimizing surgical complications and ultimately improve the surgical outcomes. Pediatric urologists need to be ready to adopt these novel devices and intraoperative techniques. This review illustrates the most promising techniques and innovative devices to enhance the surgical treatment of pediatric urolithiasis, aiming to enhance early adoption and more research on this topic for the benefit of children.